Tingkat Kepedulian Orangtua Terhadap Pemberian Susu Pada Masa Pertumbuhan Anak Usia Sekolah - Hartanti, Niken; Aprilia, Salsabila; Nuha, Chiquita Ashlaha; Afifah, Vika Fathiara; Rahmatunisa, Risma; Rupidara, Fensca Maria (Jurnal Gizi dan Kuliner, 2022)
Abstract Milk is a source of protein that has high quality because of its complete nutritional content such as protein around 3.5% with fat content around 3.0-3.8%. Milk is also a good source of phosphorus and is very rich in calcium. However, the level of milk consumption in Indonesia is still relatively low. According to the Central Statistics Agency (BPS), milk consumption in Indonesia is only 12.1 L/capita per year. Thus, milk consumption in Indonesia, especially in school-age children, needs special attention. This study aims to determine the level of parental concern for giving milk to school-age children. This study used a descriptive-analytical method design by using a questionnaire. The results showed that giving milk to school children was recommended to consume milk in one day. Therefore, it can be concluded that parents care about giving milk to school-age children. Keywords : level of concern, Growth Period, Milk